Utility of Indian Fruits in Cancer Prevention and Treatment: Time to Undertake Translational and Bedside Studies - Prabhakar, Pankaj; Pavankumar, Giriyapura S.; Raghu, Shamprasad Varija; Rao, Suresh; Prasad, Krishna; George, Thomas; Baliga, Manjeshwar Shrinath (Current Pharmaceutical Design, 2022)
The World Health Organization predicts a 70% increase in cancer incidents in developing nations over the next decade, and it will be the second leading cause of death worldwide. Traditional plant-based medicine systems play an important role against various diseases and provide health care to a large section of the population in developing countries. Indigenous fruits and their bioactive compounds with beneficial effects like antioxidant, antiproliferative, and immunomodulatory are shown to be useful in preventing the incidence of cancer. India is one of the biodiversity regions and is native to numerous flora and fauna in the world. Of the many fruiting trees indigenous to India, Mango (Mangifera indica), Black plum (Eugenia jambolana or Syzygium jambolana), Indian gooseberry (Emblica officinalis or Phyllanthus emblica), kokum (Garcinia indica or Brindonia indica), stone apple or bael (Aegle marmelos), Jackfruit (Artocarpus heterophyllus), Karaunda (Carissa carandas) and Phalsa (Grewia asiatica), Monkey Jackfruit (Artocarpus lakoocha) and Elephant apple (Dillenia indica) have been shown to be beneficial in preventing cancer and in the treatment of cancer in validated preclinical models of study. In this review, efforts are also made to collate the fruits' anticancer effects and the important phytochemicals. Efforts are also made to address the underlying mechanism/s responsible for the beneficial effects of these fruits in cancer prevention and treatment. These fruits have been a part of the diet, are non-toxic, and easily acceptable for human application. The plants and some of their phytochemicals possess diverse medicinal properties. The authors propose that future studies should be directed at detailed studies with various preclinical models of study with both composite fruit extract/juice and the individual phytochemicals. Additionally, translational studies should be planned with the highly beneficial, well-investigated and pharmacologically multifactorial amla to understand its usefulness as a cancer preventive in the high-risk population and as a supportive agent in cancer survivors. The outcome of both preclinical and clinical studies will be useful for patients, the healthcare fraternity, pharmaceutical, and agro-based sectors.
Keywords: Artocarpus lakoocha